Improving the Reliability of V-Wave Responses in the Soleus Muscle. Issue 2 (March 2019) - Mendonca, Goncalo V.; Teodósio, Carolina; Mouro, Miguel; Freitas, Sandro; Mil-Homens, Pedro; Pezarat-Correia, Pedro; Vila-Chã, Carolina
Abstract : Purpose: The V wave is an electrophysiologic variant of the H reflex that is evoked with supramaximal stimulus intensity. In this study, we explored whether the between-day reliability of V-wave normalized amplitude varies as a function of the number of intrasession measurement trials. We also determined whether the reliability of the V wave improves after the exclusion of the initial testing trials. Methods: Eighteen healthy, young participants (10 men and 8 women) were included in this study. Test–retest reliability was assessed using intraclass correlation coefficients and the standard error of the measurement (1.96*SEM). Results: The intraclass correlation coefficient values of the V-wave normalized amplitude increased in a progressive fashion with the inclusion of more than two measurement trials (from 0.41 to 0.75). The 1.96*SEM scores also decreased from 12.47% to 7.60% after calculating the V-wave normalized amplitude from five versus two measurement trials. After excluding the first two trials from V-wave calculations, the intraclass correlation coefficient and the 1.96*SEM score attained values of 0.88 and 6.54%, respectively. Conclusions: Our findings indicate that the test–retest reliability of the V-wave response increases in a progressive fashion with more than two intrasession measurement trials (up to five trials). It also shows that to ensure maximal reliability, the first two measurement trials should be discarded from V-wave computations.